Correlation between Chest CT Score and Outcome of COVID-19 Patients: Experience from A COVID Hospital of Chattogram, Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2021)
Background: Studies elsewhere in the world observed that, chest Computed Tomography (CT) scoring could help to stratify patient’s risk and predict short-term outcome of patients with COVID-19 pneumonia. But report from Bangladesh in this regard is in short supply. This study was aimed to investigate the relationship between the percentage of lung involvement as defined by CT scan score and outcome of COVID-19 patients admitted in a COVID dedicated hospital of Bangladesh.Materials and methods: This prospective observational study included 103 RTPCR confirmed COVID19 patients admitted in Chittagong Medical College Hospital (CMCH). All patients had a non-contrast HRCT scan done at presentation. Severity of CT score was categorized as Mild: score 7 or less, Moderate: score 8–17 and severe: score 18 or more. Outcome data in terms of oxygen requirement, length of hospital stay and in-hospital mortality were collected.Results: The mean age was 53.12 ± 12.69 years (58.3% males, 41.7% females). CT severity score was found to be positively correlated with clinical category of COVID-19. The oxygen requirements and length of hospital stay were increasing with the increase in scan severity. Multivariate analysis revealed that CT severity score was the only significant predictor for death (Odds ratio: 1.228; 95% CI:1.019-1.48).Conclusions: Our data suggest that chest CT scoring system can aid in predicting COVID-19 disease outcome and significantly correlates with oxygen requirements in a sample of Bangladeshi COVID-19 patients.JCMCTA 2021 ; 32 (1) : 78-82